Fault Pattern and Seismotectonic Style of the Campania – Lucania 1980 Earthquake (Mw 6.9, Southern Italy): New Multidisciplinary Constraints - Bello, S.; de Nardis, R.; Scarpa, R.; Brozzetti, F.; Cirillo, D.; Ferrarini, F.; di Lieto, B.; Arrowsmith, R. J.; Lavecchia, G. (Frontiers in Earth Science, 2021)
New fault trace mapping and structural survey of the active faults outcropping within the epicentral area of the Campania-Lucania 1980 normal fault earthquake (Mw 6.9) are integrated with a revision of pre-existing earthquake data and with an updated interpretation of the CROP 04 near-vertical seismic profile to reconstruct the surface and depth geometry, the kinematics and stress tensor of the seismogenic fault pattern. Three main fault alignments, organized in high-angle en-echelon segments of several kilometers in length, are identified and characterized. The inner and intermediate ones, i.e. Inner Irpinia (InIF) and Irpinia Faults (IF), dip eastward; the outer Antithetic Fault (AFA) dips westward. Both the InIF and the IF strike NW-SE along the northern and central segments and rotate to W-E along the southern segments for at least 16 km. We provide evidence of surface coseismic faulting (up to 1m) not recognised before along the E-W segments and document coseismic ruptures with maximum vertical displacement up to ~1m where already surveyed from other investigators 40 years ago. Fault/slip data from surface data and a new compilation of focal mechanisms (1980-2018) were used for strain and stress analyses to show a coherent NNE-directed least principal stress over time and at different crustal depths, with a crustal-scale deviation from the classic SW-NE tensional direction across the Apennines of Italy. The continuation at depth of the outcropping faults is analysed along the trace of the CROP-04 profile and with available hypocentral distributions. Integrating all information, a 3D seismotectonic model, extrapolated to the base of the seismogenic layer, is built. It outlines a graben-like structure with a southern E-W bend developed at depth shallower than 10-12 km, at the hanging wall of an extensional NE- to E-dipping extensional basal detachment. In our interpretation, such a configuration implies a control in the stress transfer during the 1980 earthquake ruptures and provides a new interpretation of the second sub-event, occurred at 20 seconds. Our reconstruction suggests that the latter ruptured a hanging-wall NNE-dipping splay of the E-W striking main fault segment and possibly also an antithetic SSW-dipping splay, in two in sequence episodes.